The Instagram Effect: How Social Media Shapes Students’ English Language Skills - Nusi, Budiarto; Otoluwa, Moon Hidayati; Luwiti, Sri Rumiyatiningsih (Jurnal Bahasa, Sastra, dan Budaya, 2025)
Social media has become a significant tool for language learning in the digital era. This study focuses on three features of Instagram Reels, Stories, and Feeds with the aim of investigating how students of the English Language Education Study Program perceive the platform’s influence on their English language skills. A qualitative method was employed using semi-structured interviews with ten participants. The results indicate that Instagram supports the development of various English language skills, including vocabulary acquisition, grammar understanding, and increased confidence in speaking and writing. Participants reported that educational content from English learning accounts made their engagement with the language more informal yet effective. However, they also highlighted the importance of balancing social media use with conventional learning methods to avoid distractions. This study concludes that Instagram can be a supportive and engaging medium for English language development when used appropriately.Budiarto Nusi a [1], Moon Hidayati Otoluwa b , Sri Rumiyatiningsih Luwiti[1]  Corresponding author name: Budiarto Nusi    E-mail address: Budiartonusi061101@gmail.com